PERANCANGAN SISTEM INFORMASI PENGGAJIAN PEGAWAI BERBASIS WEBSITE (STUDI KASUS : KORP BRIMOB RESIMEN II KEDUNG HALANG, BOGOR) - Dama Sepriantama; Wiwin Winarti (CV. Multi Kreasi Media, 2024)
A payroll system is a system that can help companies to manage matters related to employee salaries, as well as to record and store employee salary payment data within an organization or company. A payroll system is really needed in a company to manage the salaries or wages of employees in the company. The system currently used at the Kedung Halang Bogor Regiment II Brimob Corps still uses a conventional system or Microsoft Excel so that payroll data is still not archived optimally. To handle this, a computerized payroll information system was created which is used to manage and record various employee payroll transactions that will be paid. Payroll information system that can produce or manage employee salary and employee absenteeism data. This Information System was created using the Waterfall Method so that it can be done in a structured manner with the rules of the method used. The results of designing this payroll information system show that the role of the information system is very important as a support in improving the quality of data processing activities, inputting employee salaries in a company. It can be concluded that by creating a web-based employee payroll information system, employee data can be stored and not easily lost because it is computerized. This web-based payroll information system makes it easier for officers to input employee salary data at the Brimob Regiment II Corps so that employee salary reports are well maintained in the database. To increase work effectiveness and provide information quickly and accurately, this information system was built using the PHP programming language, the CodeIgniter Framework and MySql as the database.